Flow‐mediated dilatation, using time course data, shows maturation of the brachial artery from young children to mid‐adolescents. (March 2015) - Kontos, Anna; Pamula, Yvonne; Martin, James; Gent, Roger; Lushington, Kurt; Baumert, Mathias; Willoughby, Scott; Richardson, Malcolm; Couper, Jennifer; Kennedy, Declan
Summary Flow‐mediated dilatation (FMD) is a tool widely used to measure arterial responsiveness to sheer stress. However, there is scant literature to show how the peripheral arterial response changes as the vascular system matures. One reason for this is that the feasibility of measuring FMD in younger children has not been established. The aim of the present study was to assess brachial artery function at rest and during the FMD response after 4 min ischaemia of the forearm in children aged 6–15 years. Time to reach maximum FMD (FMDmax) was found to be correlated with age (r = 0.4, P < 0.05), resting brachial artery diameter (r = 0.4, P < 0.05), height (r = 0.4, P < 0.05), body mass index (BMI; r = 0.45, P < 0.05), body surface area (r = 0.44, P < 0.05) and resting blood flow (r = 0.37, P < 0.05). However, there was no correlation between the traditional FMD response at 60 s or FMD maximal dilation and age, resting brachial artery diameter, height, weight, BMI, body surface area and resting blood flow. In conclusion, the time taken to reach the maximal dilation response is related to age, brachial artery luminal diameter and body habitus, but not the traditional measure of FMD response at 60 s or the maximal dilatation percentage.